cDNA-AFLP ANALYSIS REVEALS DIFFERENTIAL GENE EXPRESSION IN RESPONSE TO SEED AGING IN SIBERIAN WILDRYE - H. Wang1; C. Guan2; Y. Q. Han; Y. Liu; F. G. Mi; Y. W. Zhang (Journal of Animal and Plant Sciences, 2020)
Siberian wildrye (Elymus sibiricus L.) is widely cultivated in the central and western regions of China. It is an important agricultural produce and utilized in animal feed and is also important for ecological environment protection. It is of great significance for the preservation and production of germplasm resource to elucidate the seed aging mechanism, such as delaying seed aging, prolonging seed life as well as repairing seed vigor. Information on seed aging including aging conditions, physiological and biochemical characteristics, damage to genomic DNA and genetic integrity of germplasm resource is limited but necessary for germplasm collection, conservation and effective commercial use. However, it is rarely reported on the transcriptome analysis of seed aging in Siberian wildrye. In this study, we analyzed the differentially accumulated TDF (Transcript-Derived Fragments) by cDNA-AFLP technique using 136 pairs primers, a total of 653 TDFs were identified. These up-regulated TDFs were picked for sequence alignment and functional analysis. The results showed that the sequences of TDFs are highly homologous in plants, which are pyruvate kinase, metal transport protein, DNA damage repair protein, lectin receptor kinase, and leucine zip transcription factor. Additionally, chloroplast structure was destroyed and energy consumption was increased in seed aging, at the same time, it could resist aging by increasing transcripts of relevant defense genes transporter genes and corresponding DNA damage repair genes when Siberian wildrye is aged. The purpose of this study was to provide a theoretical basis for revealing the potential aging mechanism of Siberian wildrye from the transcriptional level.
Keywords: Siberian wildrye; seed aging; cDNA-AFLP; transcript-derived fragments (TDFs)